The basis of updated knowledge is a tool of activate learning (Eurasian Journal of Philology Science and Education, 2018)
The article deals with of modern education. The characteristics and content of the textbooks basedon the content of the updated education, the advantages of their textbooks have been analyzed. Thepurpose of comprehensive to develop of the students through reading, listening, speaking and writingactivities of the textbooks, analyzes have been made that the subject is guided by the basic principles ofscience, systemicity, consistency, consciousness, visibility, etc. Questions of reading, listening texts areproblematic. The textbook’s teaching materials are joined into scientific and social issues and their ownanalysis of the various theoretical methods of their solution. It has been concluded that the problematicissues and questions are based on the age characteristics of the learner and that before the introductionof the text, the questioning of the questions leads to the student’s cognitive ability, creativity, and thestudent’s active involvement in the learning process